2021
DOI: 10.1155/2021/6680455
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Learning and Semisupervised Adversarial Detection and Classification of COVID‐19 in CT Images

Abstract: The ongoing coronavirus 2019 (COVID-19) pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has resulted in a severe ramification on the global healthcare system, principally because of its easy transmission and the extended period of the virus survival on contaminated surfaces. With the advances in computer-aided diagnosis and artificial intelligence, this paper presents the application of deep learning and adversarial network for the automatic identification of COVID-19 pneumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…The authors of [17] studied the classification of CT scans based on TL using five pre-trained networks: DenseNet, Inception, MobileNet, ResNet50, and VGG16. The TL was adopted in these networks to enhance the performance as the authors worked on small datasets in order to eliminate the network training from scratch and avoid the large complexity of training.…”
Section: Related Workmentioning
confidence: 99%
“…The authors of [17] studied the classification of CT scans based on TL using five pre-trained networks: DenseNet, Inception, MobileNet, ResNet50, and VGG16. The TL was adopted in these networks to enhance the performance as the authors worked on small datasets in order to eliminate the network training from scratch and avoid the large complexity of training.…”
Section: Related Workmentioning
confidence: 99%
“…Elhia et al [35] proposed a nonlinear model to control coronavirus spreading in Morocco city. Oluwasanmi et al [36] demonstrated the use of deep learning and adversarial network to detect COVID-19 pneumonia in computed tomography scans of the lungs. ey obtained very satisfactory results.…”
Section: Complexitymentioning
confidence: 99%
“…Eight pre-trained CNN models were assessed for this purpose. In [13], the authors presented transfer learning and the adversarial network on CT scans to annotate COVID-19 and Pneumonia images. An alternative modeling system described as DeTraC was suggested in [14].…”
Section: Introductionmentioning
confidence: 99%